A Study on Particulate Matter Mass Concentration in Selected Indoor Environment at School Near to Quarry Area - Shamsudin, Nur Syafawani (2016)
Air pollution is defined as the presence of any air pollutant in the air that is potential to cause health effect or cause harm to the environment. A study was conducted to investigate the exposure levels of air pollutants and their relationship between the quarry distance and schools in Jeli state. The method used in this study includes measuring the concentration of air pollutants, namely PM₁₀. Two sampling location were chosen to measure the concentrations of indoor air pollutants. Those sampling location are SK Legeh which act as control site and SK Gual Jedok as exposure site. Classrooms and offices were chosen for each school as sub-locations to measure the PM₁₀ mass concentration. Low-volume air sampler and sampling devices is used to measure the indoor PM₁₀ mass concentration. This study found that indoor PM₁₀ mass concentration recorded was inconsistent for every 20 days at each location whose there were concentration of PM₁₀ exceed the standard limits of indoor PM₁₀ mass concentration which is 0.15 mg/m", Average PM₁₀ mass concentrations in classroom at SK Legeh and SK Gual Jedok were in the range of 0.0417 - 0.125 mg/nr' and 0.0417 - 0.167 mg/m3 respectively. Whereas PPM₁₀ mass concentration obtained in office at SK Legeh and SK Gual Jedok were 0.0104 - 0.0615 mg/nr' and 0.0208 - 0.0938 mg/m3 respectively. From the statistical analysis, there is significant difference of PM₁₀ mass concentration between classroom at SK Legeh and classroom at SK Gual Jedok with reading of 0.075 ± 0.035 mg/m" and 0.117 ± 0.069 mg/m". In conclusion, the air quality for both of schools can be considered as good and safe level.